Določanje vezalne energije pasti za vodik z visokotemperaturno vakuumsko ekstrakcijo - Vehovar, Leopold (Kovine zlitine tehnologije, 1997)
The interaction of hydrogen with transition metals and their carbides was studied by thermal analysis using gas chromatograph as hydrogen detector. The trap binding energy was determined. Results show that the Nb or Mo carbides in microalloyed steels have the lowest trap binding energy. NIOMOL 490 K steel alloyed by Nb and Mo have shown the best resistance to hydrogen embrittlement.
Keywords: jekla; molibden; niobij; vodik; preiskava materiala; vodikova krhkost; kemijska kinetika; adsorpcija